Identify Key Drivers of Patient Dissatisfaction: Applying Importance-Performance Mapping Analysis (IPMA) - Santoso, Anita Sevira; Antonio, Ferdi (SAFE-Network, 2025)
This study aims to identify the key factors contributing to patient dissatisfaction in six general hospitals operated by security institutions in East Java using the Importance–Performance Mapping Analysis (IPMA). Patient dissatisfaction generally arises from three categories of issues—clinical, management, and relational problems that influence patients’ experiences during hospitalization. Using a purposive sampling method, data were collected from 130 inpatients who had previously submitted complaints. The analysis indicates that clinical issues, particularly indicators related to the adequacy of pain management and the appropriateness of hospital meals (CPQY4 and CPQY5), fall within the high-importance and low-performance quadrant, making them the primary priorities for service improvement. Meanwhile, several indicators within the management and relational problem categories, such as RPCN2 and MPET4, demonstrate high performance but have a low impact on dissatisfaction, suggesting that these aspects are functioning well but are not the principal determinants of patient dissatisfaction. The implementation of this study includes recommendations to enhance clinical competence through integrated training programs, regular medical audits, and the refinement of complaint-handling procedures to ensure a more proactive and responsive approach. Additionally, strengthening interpersonal communication, improving inter-unit coordination, and conducting routine evaluations using IPMA are proposed to help hospitals more accurately target improvement priorities and support the development of patient-centered healthcare services.